Manifestation of Mental Disorder of Janu Character in the Novel Manusia dan Badainya by Syahid Muhammad: A Psychopathological Perspective - Niranda Oki; Herman Didipu; Ayu Hidayanti Ali (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the types of mental disorders experienced by the character Janu in the novel Manusia dan Badainya by Syahid Muhammad. Mental disorders are analyzed using a psychopathology perspective to reveal the complexity of the character’s psychological condition. The research data source is the entire 300-page novel, while specific data are in the form of narrative excerpts and dialogues that indicate mental disorders. The main research instrument is the researcher himself, assisted by a data classification table based on psychopathology theory. The data analysis technique applies a literary psychology approach by integrating structural analysis focusing on the elements that build the story and psychological analysis. The results of the study indicate that the character Janu experiences four types of mental disorders that are interrelated. First, anxiety disorder characterized by excessive fear and panic attacks. Second, depressive disorder as the most dominant manifestation, including withdrawal from the environment, lack of appetite, self-blame, a desire to give up, unstable moods, and loss of enthusiasm for self-care. Third, post-traumatic stress disorder is reflected in emotional reactions to traumatic triggers and avoidance behavior. Fourth, adolescent stress disorder is manifested through unhealthy emotional dependence on partners and a poor relationship with the mother. These four types of disorders reinforce each other, making Janu’s psychological burden increasingly complex and difficult to unravel. This finding enriches the study of literary psychology, particularly in representing the mental health of fictional teenage characters.